Bullying in children: impact on child health - Richard Armitage (BMJ Publishing Group, 2021)
Bullying in childhood is a major public health problem that increases the risk of poor health, social and educational outcomes in childhood and adolescence. These consequences are felt by all those involved in bullying (bullies, victims and bully-victims) and are now recognised to propagate deep into adulthood. Cyberbullying is a relatively new type of bullying in addition to the traditional forms of direct physical, direct verbal and indirect bullying. Children who are perceived as being 'different' in any way are at greater risk of victimisation, with physical appearance being the most frequent trigger of childhood bullying. Globally, one in three children have been bullied in the past 30 days, although there is substantial regional variation in the prevalence and type of bullying experienced. The consequences of childhood bullying can be categorised into three broad categories: educational consequences during childhood, health consequences during childhood and all consequences during adulthood. Many dose-response relationships exist between the frequency and intensity of bullying experienced and the severity of negative health consequence reported. The majority of victims of cyberbullying are also victims of traditional bullying, meaning cyberbullying creates very few additional victims. Overall, adverse mental health outcomes due to bullying in childhood most severely impact on bully-victims. Bullying prevention is vital for the achievement of the Sustainable Development Goals, with whole-school cooperative learning interventions having the strongest evidence base for successful outcomes. Clear management and referral pathways for health professionals dealing with childhood bullying are lacking in both primary and secondary care, although specialist services are available locally and online.